Kandungan Senyawa Aktif dan Daya Antibakteri Daun Sambung Darah (ACTIVE COMPOUNDS AND ANTIBACTERIAL ACTIVITY OF EXCOECARIA AGALLOCHA) - Poeloengan, Masniari; ., Andriani (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
Sambung darah (Excoecaria agallocha L.) leaves are often used as traditional medicine. This experimentwas done to analyze the compounds of E. agallocha extract against  antibacterial activity either on Grampositive bacteria (Staphylococcus aureus, S.  epidermidis, and Streptococcus agalactiae), and Gram negativebacteria  (Escherichia coli and Salmonella sp.). Leaves extract of E. agallocha L. Was diluted with or madewith methanol percolation. Antibacterial activity test was performed by using paper diffusion, whileminimum concentration test was done by using dilution method. The result show that compounds ofsambung darah leaves extract were alkaloid, tanin, flavonoid, tritefenoid, glicosida and saponin. Sambungdarah extract has antibacterial activity on Gram positif bacteria (S. aureus, S. epidermidis, S agalactiae),where as it has not antibacterial activity against Gram-negative bacteria (E. coli and Salmonella sp.).
Keywords: Excoecaria agallocha, antibacterial, Gram positif bacteria, Gram negative bacteria.